A legal research on the efficacy of domestic violence Act 1994 / Azweena Iqmar Johan Adam Jurohni, Nadzatul Amirah Hashim and Shamir Farrahin Shapri - Johan Adam Jurohni, Azweena Iqmar; Hashim, Nadzatul Amirah; Shapri, Shamir Farrahin (2011)
No one should be denied their rights or be mistreated. Nowadays, more cases on domestic violence against women and also mistreatment of wives have been reported and it is not a new phenomenon anymore. Although there are statutes and rules available to protect these victims, yet this issue still happens and became worst. The Domestic Violence Act 1994 was passed by Parliament in 1994 and was put into implementation in June 1996. In spite of the introduction of this Act, many non-governmental organisations of the opinion that this Act still need to be reform as it have many weaknesses and loopholes. Therefore, this research is focusing on the adequacy of the protection provided to the victim of Domestic Violence Act 1994 and this project touched about laws and its components. The importance of literature reviews is to get a better understanding of the topic to achieve the objectives of this study. In addition, it helps to get more information such as from journals or articles. This project paper contains the information on Domestic Violence Act 1994 on its interpretation and administrative procedures. Furthermore, this project paper also concentrates on the analysis of any weaknesses sections of this Act that need to be amend to give a better scope and protection to the victim. The proposed outcome from this research is that we expect to find out solutions to handle this issue from getting worst in order to bring back the social values in our country.